2022
DOI: 10.1007/s11301-022-00297-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit capacity and social performance: mapping the field and future directions

Abstract: Nonprofit organizations are critical actors in the Sustainable Development Goals as they provide a wide range of social services to the community and contribute to creating a sustainable future. They must compete for funding or government contracts by showing high social performance. Among the top factors influencing social performance is capacity, and it has received considerable attention in public and nonprofit literature. Capacity refers to the resources, capabilities, and practices required to perform the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 196 publications
2
6
0
1
Order By: Relevance
“…Hypothesis H2 is supported. This study is therefore in line with the literature already mobilized on the subject (Jiao, 2021;Nordin et al, 2022). However, the fact that NPOs are subject to regulatory pressures that lead them to adopt plans for training or better integration of people in difficulty should not be underestimated.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hypothesis H2 is supported. This study is therefore in line with the literature already mobilized on the subject (Jiao, 2021;Nordin et al, 2022). However, the fact that NPOs are subject to regulatory pressures that lead them to adopt plans for training or better integration of people in difficulty should not be underestimated.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies have empirically confirmed this link (Bagnoli and Megali, 2011;Bradford et al, 2020), while pointing out that it is often found in the medium term. More indirectly, studies have also shown that accountability strengthens non-profit capacity and social performance (Nordin et al, 2022;Stainer and Stainer, 2000). In this, H2.…”
Section: Hypothesis Development: Recent Developments On Accountabilitymentioning
confidence: 91%
“…Las tres primeras publicaciones han aparecido tradicionalmente en estudios bibliométricos centrados en ESFL (v.gr. Lu et al, 2019;LePere-Schloop, M., & Nesbit, 2022;Nordin et al, 2022). Con la excepción de las dos últimas publicaciones, el resto solamente publican trabajos sobre empresa social, en la medida en que existe mención al término nonprofit.…”
Section: Resultsunclassified
“…The public administration suffered from a lack of organizational learning and recognition of local initiatives. On the other hand, based on recent research on non-profit capacity (Nordin et al, 2022 ), some lessons can be drawn. First, the dependence of NPOs on volunteers largely explains the organizational failures.…”
Section: Discussionmentioning
confidence: 99%